ASSOCIATION BETWEEN GENOTYPE AND DISEASE PROGRESSION IN ITALIAN STARGARDT PATIENTS: A Retrospective Natural History Study. Issue 7 (July 2019) - Di Iorio, Valentina; Orrico, Ada; Esposito, Gabriella; Melillo, Paolo; Rossi, Settimio; Sbordone, Sandro; Auricchio, Alberto; Testa, Francesco; Simonelli, Francesca
Abstract : Purpose: To investigate the natural history of Stargardt disease over a multiyear follow-up. Methods: We reviewed medical records of Stargardt disease patients, with clinical diagnosis of Stargardt disease at a single institution, which was also supported by molecular diagnosis. All patients underwent best-corrected visual acuity, fundus photography, optical coherence tomography, and full-field electroretinography. Results: The study cohort consisted of 157 Stargardt disease patients aged 30.4 ± 1.1 years. Longitudinal analysis (mean follow-up: 3 years) showed a significant worsening of best-corrected visual acuity at an average rate of 1.5 Early Treatment Diabetic Retinopathy Study letters/year ( P < 0.001), an enlargement of retinal pigment epithelium lesion area by optical coherence tomography at an average linear rate of 0.10 mm 2 /year ( P < 0.001), and a thinning of central macular thickness at a mean rate of −1.42 μ m/year ( P < 0.001). Survival analysis showed that patients with 2 alleles harboring likely-null variants, on average, reached most severe disease stage, i.e., legal blindness, alteration in both dark-adapted and light-adapted electroretinographic responses, and retinal pigment epithelium lesion area larger than 2.5 mm 2 significantly earlier than patients with at least one allele harboring a missense variant. Conclusion: The current longitudinal study showed a significant genotype–phenotype correlation characterization, because patients harboring 2 likely-null alleles reach a severe disease stage about 10 years earlier than patients with at least one missense allele. Abstract : Supplemental Digital Content is Available in the Text.The current longitudinal study investigates natural history of Stargardt disease in a large Italian cohort in relationship with the genotype, showing a faster progression of visual function loss and of retinal atrophy in patients that harbor two likely null mutations.